Effects of high pressure modification on conformation and gelation properties of myofibrillar protein - Zhang, Ziye; Yang, Yuling; Zhou, Peng; Zhang, Xing; Wang, Jingyu (Food chemistry, 2017)
•Higher pressures induced greater denaturation and unfolding of proteins.•Moderate high pressure (≦200MPa) strengthened protein functionality.•Stronger high pressure (⩾300MPa) weakened protein functionality.•200MPa was the optimum pressure for modification to improve functionality. The effects of high pressure (HP) treatment (100–500MPa) on conformation and gelation properties of myofibrillar protein (MP) were investigated. As pressure increased (0.1–500MPa), α-helix and β-sheet changed into random coil and β-turn, proteins unfolded to expose interior hydrophobic and sulfhydryl groups, therefore surface hydrophobicity and formation of disulfide bonds were strengthened. At 200MPa, protein solubility and gel hardness reached their maximum value, particle size had minimum value, and gel microstructure was dense and uniform. DSC data showed that actin and myosin completely denatured at 300MPa and 400MPa, respectively. Rheological modulus (G′ and G″) of HP-treated MP decreased as pressure increased during thermal gelation. Moderate HP treatment (≦200MPa) strengthened gelation properties of MP, while stronger HP treatment (⩾300MPa) weakened the gelation properties. 200MPa was the optimum pressure level for modifying MP conformation to improve its gelation properties.